Depressive Syndromes in Autoimmune Disorders of the Nervous System: Prevalence, Etiology, and Influence - Liu, Yanjun; Tang, Xiangqi (Frontiers in Psychiatry, 2018)
Autoimmune diseases of the nervous system (ADNS) consist of a group of severely disabling disorders characterized by abnormal immune attack against protein components of the nervous system. This type of attack behavior may occur in the central or peripheral nervous system, and in the neuromuscular junction, resulting in neuronal damage, axonal injury, demyelination or destruction of the neuromuscular junction. While the neurological deficits of patients with ADNS have received significant research attention, the manifestation of depression tends to be ignored. In fact, depressive manifestation is common in ADNS and adds significant burden upon patients suffering from this disease. Here, we systematically reviewed the current literature to highlight the prevalence, etiology and influence of depressive manifestation in ADNS. Most autoimmune diseases of the nervous system are discussed in this paper, from multiple sclerosis, acute disseminated encephalomyelitis and autoimmune encephalitis to acute myelitis, neuromyelitis optica, Guillain-Barré syndrome and myasthenia gravis. Depressive symptoms usually develop as a comorbidity during the course of disease, but sometimes exist as a primary presentation of the disease. Psychosocial factors, long periods of disablement and chronic pain are the three most common causes of depressive symptoms in many chronic conditions, particularly in peripheral neuropathy. Furthermore, the higher prevalence of depressive symptoms in ADNS suggests that immunological dysregulation may contribute to the elevated morbidity of depression. Finally, structural lesions of the brain, and some medications for ADNS, are also thought to precipitate depressive states in ADNS.